If I've read your question correctly, you need to subtract: a2 +2a -7 a2 -4a2 +5a2 -6 = 2a2 -6 Note, if x - y = z, then y = x - z; so: 2a2 -6 - (a2 -2a +1) = 2a2 -6 - a2 +2a -1 = a2 +2a -7
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b
2
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)
= 3 X 2 = 6 = a X a = a2 (a square) = 6a2 + 5 Answer
If I've read your question correctly, you need to subtract: a2 +2a -7 a2 -4a2 +5a2 -6 = 2a2 -6 Note, if x - y = z, then y = x - z; so: 2a2 -6 - (a2 -2a +1) = 2a2 -6 - a2 +2a -1 = a2 +2a -7
(a2 + a + a2) = (2a2 + a) = a (2a + 1)
2A plus 3B times 2A - 3B = 4A2 - 9B2; this is an example of the general formula (a + b)(a - b) = a2 - b2.
ANS:(a-3)(a+1)
If its 2a=8 then a= 4 If a=8 then a2=16 If 8=D then 8=====================================D
a2(2a2-21a+49) a2(2a-7)(a-7)
a2-36=0 2a=36 a=36/2 a=18 Hence, the required value is a is 18.
a≠ 0,LCD = a33/a + 2/a2 - 1/a3= (3/a)(a2/a2) + (2/a2)(a/a) - 1/a3= 3a2/a3 + 2a/a3- 1/a3= (3a2 + 2a -1)/a3
(a2 + 5a + 6)/(a - 2) = (a + 2)*(a 3)/(a - 2) which cannot be simplified further. It can, however be written as (a2 - 2a + 7a - 14 + 20)/(a - 2) which is (a + 7) + 20/(a - 2)
(a - 5)(a + 3) = a2 - 2a - 15
a(a + 2) = a2 + 2a
2a3-16a2+30a Factor out 2a: 2a(a2-8a+15) (2a)(a-5)(a-3) This is the most factored form of this expression.